2021
DOI: 10.3390/su13073889
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Dimensional Hybrid Learning Environment for Business Education: A Knowledge Dynamics Perspective

Abstract: The main promise of new, digitally enabled and hybrid learning environments is to enable future-ready knowledge workers by equipping them with business and digital competences. However, business education (BE) research often focuses on the problems of instructional design and individual disciplines, rather than on the challenges of developing a holistic knowledge and competences required to ensure students’ long-term employability. This paper, to address this gap, approaches BE as a knowledge dynamics field th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In education, technological developments are driving demand redesigning learning spaces that would extend to digital environments (Latorre-Cosculluela et al, 2021). Digital technologies enable virtual learning environments, distant learning, or hybrid learning (Balyer and Öz, 2018;Pavlidou et al, 2021). The nature of digital work and learning becomes much more virtual and dynamic, allowing for more flexibility, autonomy, and new dynamics of experiences (Brahma et al, 2020;Verganti et al, 2020;Pavlidou et al, 2021).…”
Section: Organisations In the Digital Worldmentioning
confidence: 99%
“…In education, technological developments are driving demand redesigning learning spaces that would extend to digital environments (Latorre-Cosculluela et al, 2021). Digital technologies enable virtual learning environments, distant learning, or hybrid learning (Balyer and Öz, 2018;Pavlidou et al, 2021). The nature of digital work and learning becomes much more virtual and dynamic, allowing for more flexibility, autonomy, and new dynamics of experiences (Brahma et al, 2020;Verganti et al, 2020;Pavlidou et al, 2021).…”
Section: Organisations In the Digital Worldmentioning
confidence: 99%
“…To realize the concept of hybrid education that combines traditional values with modern educational methods, the first thing that needs to be done is to integrate both approaches in the school curriculum (Ogunmakin, 2024). Curriculum development should take into account the learning of traditional values through relevant and engaging approaches for students, while utilizing modern educational technologies and concepts in their delivery (Pavlidou, Dragicevic, & Tsui, 2021).…”
Section: Future Hybrid Education Concepts Rooted In the Pastmentioning
confidence: 99%
“…In professional training, such an ability of finding and using up‐to‐date information for problem solving has also been highlighted (Kinsella et al., 2018 ). Researchers have indicated that most students tend to rely on what they have learned from the textbooks and, hence, might not be able to find and use the up‐to‐date knowledge when dealing with practical cases (Leighton & Griffioen, 2021 ; Pavlidou et al., 2021 ). The popularity of mobile and communication technologies has significantly affected the way of teaching and learning (Linderman et al., 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%